Pengaruh Jenis Pelarut dan Waktu Maserasi terhadap Ekstrak Kulit Biji Kakao (Theobroma cacao L.) sebagai Sumber Antioksidan - Angga Prasetya, I Wayan Gde; Ganda Putra, G.P.; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 1 (2020): Maret, 2020)
Cocoa bean husk is a waste of cocoa processing that is large enough and has not been used optimally. Cocoa bean husk waste can be used more optimally by extracting polyphenol compound and used as natural antioxidant. This research aims to determine the effect of the type of solvent and maceration time of cocoa bean husk extract as a source of antioxidants and to determine the best type of solvent and maceration time to produce cocoa bean husk extract as a source of antioxidants. This experiment uses a randomized block design with two factors. The first factor is the type of solvent consisting of methanol 95 percent, ethanol 96 percent and acetone 90 percent. The second factor is the maceration time consisting of 24, 36 and 48 hours. The data is analyzed by variant analysis and continued with the Tukey test. The results showed that the type of solvent and maceration time is a very significant effect on yield, total phenolic and antioxidant capacity. The interaction between treatment is a very significant effect on total phenolic and antioxidant capacity but did not significantly affect the yield of cocoa bean husk extract. The best treatment to produce cocoa bean husk extract as a source of antioxidants is using ethanol solvent and maceration time for 48 hours with a yield characteristic 11. 72±0.45 percent, a total phenolic at 80. 76±1.12 mg of GAE/g and Antioxidant capacity 49. 55±1.13 mg GAEAC/g. Keywords : cocoa bean husk, extraction, solvent, antioxidants.